From Value to Power: The Rise of Oil as a Political Economic Commodity - Bülent Temel (Turkish Economic Association, 2012)
This paper traces the historical trajectory of oils transformation from an economic resource into a political economic commodity. Since its beginning as an industrial raw material in the mid 19th Century, petroleum has become an increasingly significant commodity relevant to a number of domains from domestic politics to international trade, environment to foreign affairs. An historical account of the rise of oil in international political economy sheds light on the dynamics that generate the political power associated with it, the constraints that restrict the policy space for many governments in international relations today, and the unpredictable nature of its economic value.
Keywords: 330